The ArtReview’s power 100: on the concept and the constitution of power in contemporary art - Buckermann, Paul (Arts and power, 2022)
Why is there a ranking of the most influential agents in contemporary art? This article contributes to a deeper understanding of epistemologies in art worlds and does so by focusing on paradigmatic worldviews. I reconstruct the ranking Power 100’s understanding of art’s role in society, its assumed internal mechanisms and the function of power in it. My results show how the list makes sense within its own terms, because the analysis highlights the consistency of the list’s paradigmatic assumptions about a world-to-ranked and its concrete production. Furthermore, I discuss sociological concepts of power (Weber, Bourdieu, Luhmann) to argue that the list can be described as an internal perspective on the art world rather than an external understanding of it. The Power 100’s epistemology combines a deep belief in art’s positive role in society with a proto-sociological conception of symbolic (power) structures and the autonomous reproduction of the arts. Referring to research on evaluation and comparison, my empirical and theoretical results have implications for both a sociology of the arts and research on rankings.
Gesehen am 28.11.2022